Changes of T lymphocyte subsets in patients with HIV-negative symptomatic neurosyphilis. (May 2019) - Liu, Li-Li; Liu, Wen-Na; Jiang, Xiao-Yong; Jun-Ren,; Chen, Mei-Hua; Liu, Zhao-Ji; Lin, Yong; Zhu, Shao-Gang; Lin, Li-Rong; Zheng, Wei-Hong; Yan, Jiang-Hua; Yang, Tian-Ci
Abstract: Objectives: The host immune response could be an imperative factor in the pathogenesis of neurosyphilis, but the role of T lymphocyte subsets remains unclear. In the present study, we assessed the CD4 + T and CD8 + T cell subsets in the peripheral blood of patients with HIV-negative symptomatic neurosyphilis and then explored the clinical application value of neurosyphilis. Methods: In total, 24 patients with HIV-negative symptomatic neurosyphilis and 22 patients with syphilis/non-neurosyphilis were included in this study and cerebrospinal fluid (CSF) and blood samples were obtained. Th1, Th2, Th17, Th9, CD8+IFN-γ+, CD8+IL-4+, CD8+IL-9+, and CD8+IL-17 + cells were identified by flow cytometry. Results: The levels of CD8+IFN-γ+ were significantly increased in the peripheral blood of neurosyphilis patients compared to that in syphilis/non-neurosyphilis patients, but it was opposite to Th2, Th9, CD8+IL-4+, CD8+IL-9+, and CD8+IL-17 + cells. Dendritic cells (DCs) of neurosyphilis matured by T. pallidum induced the development of a combination of IFN-γ-producing Th1 cells. The number of CD8+IL-17 + cells was significantly correlated with the CSF RPR and CSF TPPA levels. ROC curve analysis revealed that the number of CD8+IFN-γ+ cells could be a potential biomarker for neurosyphilis from non-neurosyphilis/syphilis. Conclusions: High expression of CD8+IFN-γ+ cells and low expression of CD8+IL-17 + cells in patients with symptomatic neurosyphilis, which explains the pathogenesis of symptomatic neurosyphilis, meanwhile CD8+IFN-γ+ cells may be a better indicator in classifying symptomatic neurosyphilis from non-neurosyphilis/syphilis among patients without HIV infection. Highlights: The host immune response could be an imperative factor in the pathogenesis of neurosyphilis. A comparative analysis of the CD4 + and CD8 + T cell subsets in the peripheral blood of HIV-negative symptomatic neurosyphilis patients. The levels of CD8+IFN-γ+ were significantly increased in the peripheral blood of neurosyphilis patients compared to that in syphilis/non-neurosyphilis patients. CD8+IFN-γ+ cells may be a better indicator in differentiating neurosyphilis from non-neurosyphilis/syphilis patients.